Evaluation of the COVID-19 pandemic' effects on practitioners elderly physical activities: Assessment of the Covid-19 pandemic's effects on elderly - Nobre Peniche, Evelin Aline; Garcia Leal, Fábia Évine; Nogueira Dias Souza, Hildeana; Barbosa Bezerra, Juciléia (Journal of Health Care, 2023)
Introduction: The pandemic has changed the population's lifestyle. Objective: to evaluate theeffects of the COVID-19 pandemic on elderly people attending the Social Service of Commerce(SESC). Materials and methods: Quantitative research, developed with elderly people aged 60years or older. Data were collected through semi-structured interviews carried out remotely viatelephone calls with 120 elderly people, collecting information related to sociodemographic data;emotional health; physical activity and health. Results: More than 50% of participants practicingsocial isolation and said that the pandemic influenced their emotional state. There was anassociation between physical activity and hours sitting per day. Conclusion: According to theresults, the pandemic influenced the emotional aspect of the participants and those who practicedphysical activity spent less time sitting.
Keywords: Health of the Elderly; Social isolation; Sedentary behavior